Third Nerve Palsy: Rare Adverse Event following Covid-19 Vaccination - Indira Balasaheb Deshmukh; Shreyas Ramchandra Burute; Shraddha Milind Pore; Atmik Singh (Research Center for Rational Use of Drugs (RCRUD), 2024)
Drugs Controller General of India (DCGI) in April 2022 approved the emergency use authorisation of Corbevax and Covaxin COVID 19 vaccines in children. Corbevax is a protein subunit COVID 19 vaccine developed by Texas Children's Hospital.  Third nerve palsy is rarely reported following protein sub- unit COVID vaccines. We report a case of a 13-year-old male who presented to a tertiary care hospital with complaints of   giddiness, headache, diplopia and drooping of left eye within one hour of receiving Corbevax vaccine in school. He was subsequently diagnosed with third nerve palsy and treated with corticosteroids and lubricant eye drops. He recovered fully and was discharged after four days. Causality assessment as per World Health Organization (WHO) guidelines for the causality assessment of Adverse Events Following Immunization (AEFI) was consistent. Protein sub unit vaccines can rarely cause third nerve palsy.